2015
DOI: 10.1002/nbm.3426
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion MRI in the heart

Abstract: Diffusion MRI provides unique information on the structure, organization, and integrity of the myocardium without the need for exogenous contrast agents. Diffusion MRI in the heart, however, has proven technically challenging because of the intrinsic non‐rigid deformation during the cardiac cycle, displacement of the myocardium due to respiratory motion, signal inhomogeneity within the thorax, and short transverse relaxation times. Recently developed accelerated diffusion‐weighted MR acquisition sequences comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 84 publications
2
75
0
Order By: Relevance
“…Such an inverse trend was also observed in our previous studies [11] and reported in a recent high resolution (9.4-T) DTI study of the larger ovine heart [16]. This was not reported in DTI studies of healthy mouse hearts [6], likely due to insufficient resolution. The fiber orientation of the BL6 RV was slightly positive with small changes across the ventricular wall.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…Such an inverse trend was also observed in our previous studies [11] and reported in a recent high resolution (9.4-T) DTI study of the larger ovine heart [16]. This was not reported in DTI studies of healthy mouse hearts [6], likely due to insufficient resolution. The fiber orientation of the BL6 RV was slightly positive with small changes across the ventricular wall.…”
Section: Resultssupporting
confidence: 59%
“…However, in addition to its high system cost, the limited spatial resolution of DTI makes it extremely challenging for revealing detailed myocardial fiber structure in the small mouse hearts. A typical mouse heart has a diameter of ~6 mm with 1~2 mm thick ventricular wall and the myofiber orientation can change over 100° across the thin ventricular wall [6,7]. Abrupt orientation changes of more than 50° were observed between different epicardial layers [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiology is another field that uses DT‐MRI mostly to track muscle fiber orientation . The 3D architecture of the left and right ventricular myocardium has been demonstrated by DT‐MRI‐based tractography .…”
Section: Novel Bioengineering and Clinical Tools For Studying The Egjmentioning
confidence: 99%
“…Cardiac MR (CMR) diffusion tensor imaging (DTI) is a promising technique capable of probing the myocardial microstructure by assessing the myofiber orientation 1,2 . New technical developments in CMR DTI in recent years 38 have allowed the clinical application of this powerful imaging technique.…”
mentioning
confidence: 99%